2016
DOI: 10.1159/000452307
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Uptake Recovery Kinetics after the 6-Minute Walk Test in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: There is a growing interest in exercise parameters capable of objectively evaluating the functional capacity of patients with chronic obstructive pulmonary disease (COPD). Objectives: The purpose of the present study was to analyze breath-by-breath cardiopulmonary and gas exchange recovery responses of patients with COPD after a 6-minute walk test (6MWT). Methods: Oxygen uptake (VO2) kinetics of patients were obtained using mobile telemetric cardiopulmonary monitoring during and after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The correlation between the 6MWD and %DLCO has been previously reported [17]. Moreover, our results are consistent with those of a recent report showing that oxygen uptake kinetic parameters were associated with the 6MWD [18]. The functional exercise capacity of patients with COPD deteriorates in a linear fashion with disease severity assessed using GOLD staging criteria based on the %FEV1 [19].…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between the 6MWD and %DLCO has been previously reported [17]. Moreover, our results are consistent with those of a recent report showing that oxygen uptake kinetic parameters were associated with the 6MWD [18]. The functional exercise capacity of patients with COPD deteriorates in a linear fashion with disease severity assessed using GOLD staging criteria based on the %FEV1 [19].…”
Section: Discussionsupporting
confidence: 92%
“…VO 2 recovery (T 1/2 . VO 2 )) after submaximal exercise has been associated with established parameters of exercise capacity in COPD patients (13). The authors showed that the impairment of the T 1/2 VO 2 also depends on disease severity and degree of airflow limitation, suggesting that prolonged dyspnea or leg effort after exercise, commonly experienced by COPD patients, may be understood by differences in recovery ability.…”
Section: Introductionmentioning
confidence: 98%
“…In this context, previous studies have shown that . VO 2 and HR recovery kinetics are slowed in the presence of COPD (12)(13) or CHF (8-10) on isolation, as represented by t and MRT. However, to the best of our knowledge, the recovery kinetics in patients with overlapped CHF and COPD has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…In the first session, the CI and SV in the HFNC group were significantly higher than those of the NC group. The higher CI and SV might be indicative of a reduced cardiac burden in the first session training in the HFNC group (30). Our results revealed that only the NC group experienced a physiological benefit of supplemental oxygen in reducing SVR.…”
Section: Benefits Of Supplemental Oxygen Concentrationmentioning
confidence: 54%